2022
DOI: 10.3389/fnrgo.2022.935092
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive effects of prolonged continuous human-machine interaction: The case for mental state-based adaptive interfaces

Abstract: Operators of complex systems across multiple domains (e.g., aviation, automotive, and nuclear power industry) are required to perform their tasks over prolonged and continuous periods of time. Mental fatigue as well as reduced cognitive flexibility, attention, and situational awareness all result from prolonged continuous use, putting at risk the safety and efficiency of complex operations. Mental state-based adaptive systems may be a solution to this problem. These systems infer the current mental state of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 135 publications
0
5
0
Order By: Relevance
“…These ndings offered a neuroergonomics reference for interface color coding as well as contributed to uncovering brain mechanisms of color perception. In recent years, numerous researchers have employed neurometric methods to examine the cognitive activity occurring during interaction with interfaces in order to achieve optimal ergonomics [90,91]. We suggested that in addition to high levels of cognitive activity, the perceptual process is also worthy of interest, not only due to its direct impact on user experience but to its interaction with cognition.…”
Section: Discussionmentioning
confidence: 99%
“…These ndings offered a neuroergonomics reference for interface color coding as well as contributed to uncovering brain mechanisms of color perception. In recent years, numerous researchers have employed neurometric methods to examine the cognitive activity occurring during interaction with interfaces in order to achieve optimal ergonomics [90,91]. We suggested that in addition to high levels of cognitive activity, the perceptual process is also worthy of interest, not only due to its direct impact on user experience but to its interaction with cognition.…”
Section: Discussionmentioning
confidence: 99%
“…The rise of the HCI field emphasizes the connection between users and machines, primarily allowing participants in computer operations to exchange information. Existing system interfaces are generally designed to interact with a wide array of public users ( 19 ). But many systems have not been able to bring about a significant improvement in healthcare services due to issues such as poor usability or inadequate management ( 20 , 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…11 The main contribution of a state-based alarm system is that long-lasting 12 and nuisance 13 alarms can be removed; this way the workload of the operators can be lowered 14 to reduce their mental fatigue. 15 These kinds of systems are supported by machine learning algorithms to recognize alarm situations and to predict possible future scenarios by using probability values. 16 Usual state-based alarm systems need expert knowledge and first principles based on this knowledge.…”
Section: ■ Introductionmentioning
confidence: 99%
“…With the help of the proposed method, the process control system can be transformed into a so-called state-based alarm system . The main contribution of a state-based alarm system is that long-lasting and nuisance alarms can be removed; this way the workload of the operators can be lowered to reduce their mental fatigue . These kinds of systems are supported by machine learning algorithms to recognize alarm situations and to predict possible future scenarios by using probability values .…”
Section: Introductionmentioning
confidence: 99%